Temporal Trends of Persistent Organic Pollutants across Africa after a Decade of MONET Passive Air Sampling - White, Kevin B; Kalina, Jiří; Scheringer, Martin; Přibylová, Petra; Kukučka, Petr; Kohoutek, Jiří; Prokeš, Roman; Klánová, Jana (Environmental science & technology, 2021)
The Global Monitoring Plan of the Stockholm Convention on Persistent Organic Pollutants (POPs) was established to generate long-term data necessary for evaluating the effectiveness of regulatory measures at a global scale. After a decade of passive air monitoring (2008-2019), MONET is the first network to produce sufficient data for the analysis of long-term temporal trends of POPs in the African atmosphere. This study reports concentrations of 20 POPs (aldrin, chlordane, chlordecone, DDT, dieldrin, endrin, endosulfan, HBCDD, HCB, HCHs, heptachlor, hexabromobiphenyl, mirex, PBDEs, PCBs, PCDDs, PCDFs, PeCB, PFOA, and PFOS) monitored in 9 countries (Congo, Ghana, Ethiopia, Kenya, Mali, Mauritius, Morocco, Nigeria, and Sudan). As of January 1, 2019, concentrations were in the following ranges (pg/m3): 0.5-37.7 (∑6PCB), 0.006-0.724 (∑17PCDD/F), 0.05-5.5 (∑9PBDE), 0.6-11.3 (BDE 209), 0.1-1.8 (∑3HBCDD), 1.8-138 (∑6DDT), 0.1-24.3 (∑3endosulfan), 0.6-14.6 (∑4HCH), 9.1-26.4 (HCB), 13.8-18.2 (PeCB). Temporal trends indicate that concentrations of many POPs (PCBs, DDT, HCHs, endosulfan) have declined significantly over the past 10 years, though the rate was slow at some sites. Concentrations of other POPs such as PCDD/Fs and PBDEs have not changed significantly over the past decade and are in fact increasing at some sites, attributed to the prevalence of open burning of waste (particularly e-waste) across Africa. Modeled airflow back-trajectories suggest that the elevated concentrations at some sites are primarily due to sustained local emissions, while the low concentrations measured at Mt. Kenya represent the continental background level and are primarily influenced by long-range transport.
Keywords: Nigeria; polychlorované bifenyly; polychlorované dibenzodioxiny; perzistentní organické znečišťující látky; Persistent Organic Pollutants; Nigérie; dibenzofurany; Polychlorinated Biphenyls; látky znečišťující vzduch; Air Pollutants; chlorované uhlovodíky; Hydrocarbons, Chlorinated; Polychlorinated Dibenzodioxins; Environmental Monitoring; monitorování životního prostředí; Dibenzofurans